Paparan iklan televisi terhadap pemilihan makanan dan asupan energi pada anak - Yovita Puri Subardjo; Toto Sudargo; Madarina Julia (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2013)
Background: Obesity in school children is the problem of world epidemics of which its prevalence increases sharply. Food marketing through television is presumed to be one of the causing factors.Objective: To find out whether exposure to food and beverage ads through television influenced food choice and intake in children and whether its effect varied in different nutrition status.Method: The study was an experiment involving 2 experiment groups. The first group was exposed to film with food and beverage ads; the second with ads excluding foods and beverages. The children were given 8 advertised foods and drinks and 4 natural foods. The assessment was then made on energy intake and food choice. The population of the study was elementary school children at Yogyakarta Municipality and samples were selected through multi-stage random sampling. Data were analyzed descriptively and through correlation analysis.Results: Children exposed to food and beverage television ads had higher energy intake (262.7±99.7 kcal) from those on ads than children not exposed to ads (233.7±103.3 kcal), and chose more from those on ads (4.7±1.7) than children not exposed to ads (4.2±1.7). Children with normal nutrition status were influenced more by food and beverage television ads than children with over nourished and undernourished nutrition status.Conclusion: Exposure to food and beverage television ads influenced food choice and energy intake in children.